Long-Term Complications of Osteocutaneous Free Flaps in Head and Neck Reconstruction. (May 2020) - Swendseid, Brian; Kumar, Ayan; Sweeny, Larissa; Wax, Mark K.; Zhan, Tingting; Goldman, Richard A.; Krein, Howard; Heffelfinger, Ryan N.; Luginbuhl, Adam J.; Curry, Joseph M.
Objective: To determine the frequency at which patients with osteocutaneous free flap reconstruction of the head and neck develop long-term complications and identify predisposing perioperative factors. Study Design: A prospectively maintained database of free flaps performed at a single institution over a 10-year period was queried. Setting: Single tertiary care referral center. Subjects and Methods: In total, 250 osseous or osteocutaneous free flaps (OCFFs) for mandibular or maxillary reconstruction were analyzed. Data were collected on demographics, preoperative therapy, resection location, adjuvant treatment, complications, and subsequent surgeries, and multivariate analysis was performed. Subgroup analysis based on perioperative factors was performed. Results: The median follow-up time was 23 months. In 185 patients with at least 6 months of follow-up, 17.3% had at least 1 long-term complication, most commonly wound breakdown, fistula or plate extrusion (13.5%), osteoradionecrosis or nonunion (6.5%), and infected hardware (5.9%). Prior chemoradiotherapy and cancer diagnosis predisposed patients to long-term complications. At the 5-year follow-up, 21.7% of patients had experienced a long-term complication. Conclusions: Long-term complications after OCFF occurred in 17% of patients. In this series, a preoperative history of chemoradiation and those undergoing maxillary reconstruction were at high risk for the development of long-term complications and thus warrant diligent follow-up. However, OCFFs can often enjoy long-term viability and survival, even in the case of perioperative complications and salvage surgery.